Military‐related risk factors for dementia. Issue 12 (8th November 2018) - Snyder, Heather M.; Carare, Roxana O.; DeKosky, Steven T.; de Leon, Mony J.; Dykxhoorn, Derek; Gan, Li; Gardner, Raquel; Hinds, Sidney R.; Jaffee, Michael; Lamb, Bruce T.; Landau, Susan; Manley, Geoff; et al.
Abstract: Introduction: In recent years, there has been growing discussion to better understand the pathophysiological mechanisms of traumatic brain injury and post‐traumatic stress disorder and how they may be linked to an increased risk of neurodegenerative diseases including Alzheimer's disease in veterans. Methods: Building on that discussion, and subsequent to a special issue of Alzheimer's & Dementia published in June 2014, which focused on military risk factors, the Alzheimer's Association convened a continued discussion of the scientific community on December 1, 2016. Results: During this meeting, participants presented and evaluated progress made since 2012 and identified outstanding knowledge gaps regarding factors that may impact veterans' risk for later life dementia. Discussion: The following is a summary of the invited presentations and moderated discussions of both the review of scientific understanding and identification of gaps to inform further investigations.